2008
DOI: 10.1091/mbc.e07-12-1279
|View full text |Cite
|
Sign up to set email alerts
|

The Nup358-RanGAP Complex Is Required for Efficient Importin α/β-dependent Nuclear Import

Abstract: In vertebrate cells, the nucleoporin Nup358/RanBP2 is a major component of the filaments that emanate from the nuclear pore complex into the cytoplasm. Nup358 forms a complex with SUMOylated RanGAP1, the GTPase activating protein for Ran. RanGAP1 plays a pivotal role in the establishment of a RanGTP gradient across the nuclear envelope and, hence, in the majority of nucleocytoplasmic transport pathways. Here, we investigate the roles of the Nup358-RanGAP1 complex and of soluble RanGAP1 in nuclear protein trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
166
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(184 citation statements)
references
References 58 publications
(123 reference statements)
11
166
0
2
Order By: Relevance
“…One can imagine importin-␤ recognizing and binding to incoming capsids via VP1/2's nuclear localization sequence or another region on the capsid and thus carrying the capsid cargo to the nucleus. Further, Nup358 has recently been shown to play an important role in importin ␣/␤-dependent nuclear import (24). Once at the nucleus, capsid-bound importin-␤ could interact with Nup358 to anchor capsids to the NPC.…”
Section: Discussionmentioning
confidence: 99%
“…One can imagine importin-␤ recognizing and binding to incoming capsids via VP1/2's nuclear localization sequence or another region on the capsid and thus carrying the capsid cargo to the nucleus. Further, Nup358 has recently been shown to play an important role in importin ␣/␤-dependent nuclear import (24). Once at the nucleus, capsid-bound importin-␤ could interact with Nup358 to anchor capsids to the NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SUMO isopeptidases, such as SENP2, which cleave SUMO from the substrate are located at the nucleoplasmic face of the NPC (Zhang et al, 2002), suggesting a role for SUMOylation in the directionality of nucleo-cytoplasmic transport. Therefore, Nup358 is important for the translocation of molecules through the NPC (Singh et al, 1999;Hutten et al, 2008;Wälde et al, 2012;Hamada et al, 2011;Forler et al, 2004;Mahadevan et al, 2013).…”
Section: Nup358 Is a Multi-functional Platform At The Cytoplasmic Permentioning
confidence: 99%
“…RANBP2 itself does not directly participate in import, but facilitates it. In RANBP2-depleted HeLa cells, in vivo nuclear import by either Importin alpha/beta (Hutten et al, 2008) or transportin (Hutten et al, 2009) still occurs, but at substantially reduced rates. In a screening for nuclear proteins that accumulate in the cytoplasm upon RANBP2 depletion, Wälde and coworkers (2012) have also identified direct RANBP2 interactors: they found that an N-terminal fragment of RANBP2, harboring the NPC-binding domain, three FG motifs and RBD1, was sufficient to promote protein import, while neither the interaction with RANGAP1 nor the SUMO E3 ligase activity were required (Wälde et al, 2012).…”
Section: Ranbp2 In Interphase Nucleocytoplasmic Transportmentioning
confidence: 99%